Hygienic-sanitary and microbiological evaluation of açaí sold in the municipal market of Ver-o-Peso, Belém-PA, Brazil - Silva, Renata Carneiro da; Silva, Bruna Almeida da; Seccadio, Lara Lima; Pelais, Ana Carla Alves; Silva, Natácia da Silva e; Silva, Breno Mendes da (Revista de Ciências Agroveterinárias, 2023)
Açaí has great importance for the economy and diet of the population of Pará; however, there is frequent concern related to the quality of this food, since it is susceptible to various contaminations, ranging from harvesting to processing. Thus, the objective of the work was to evaluate the hygienic-sanitary conditions of the boxes that process and commercialize açaí in the municipal market, Ver-o-Peso in Belém-PA, to evaluate the microbiological quality of this product, and to verify compliance with the standards established by current legislation. For the hygienic-sanitary evaluation, a checklist was prepared with 5 evaluation blocks, 31 items and 100 verification sub-items. Microbiological analyses (molds and yeasts, Escherichia coli, Salmonella spp. and Staphylococcus aureus) were also performed on the samples collected at these points of sale. The result of the checklist showed that the adequacy rates for the blocks evaluated are below 62.5%, being classified in the regular and poor group. As for microbiological analyses, Salmonella spp. and E. coli were present, and the values for molds and yeasts and S. aureus were above what is recommended by legislation. Both evaluations were complementary tools and showed low compliance with current legislation. Therefore, consumption of this food presents a risk to consumer health.